2013
DOI: 10.1371/journal.pone.0062720
|View full text |Cite
|
Sign up to set email alerts
|

Consensus HIV-1 FSU-A Integrase Gene Variants Electroporated into Mice Induce Polyfunctional Antigen-Specific CD4+ and CD8+ T Cells

Abstract: Our objective is to create gene immunogens targeted against drug-resistant HIV-1, focusing on HIV-1 enzymes as critical components in viral replication and drug resistance. Consensus-based gene vaccines are specifically fit for variable pathogens such as HIV-1 and have many advantages over viral genes and their expression-optimized variants. With this in mind, we designed the consensus integrase (IN) of the HIV-1 clade A strain predominant in the territory of the former Soviet Union and its inactivated derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 92 publications
(119 reference statements)
1
15
0
Order By: Relevance
“…The reduced integration activity of the subtype B mutant IN B G118R had been explained by the reduced ability of the complex of this mutant with its DNA substrate to bind the DNA target [ 17 ]. As a result of natural polymorphism, INB contains Ser at position 119 and IN A contains Pro [ 21 ]. It should be noted that Ser119 is likewise present in drug-resistant strains of HIV-1 subtype C, which most often contain the G118R mutation [ 16 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced integration activity of the subtype B mutant IN B G118R had been explained by the reduced ability of the complex of this mutant with its DNA substrate to bind the DNA target [ 17 ]. As a result of natural polymorphism, INB contains Ser at position 119 and IN A contains Pro [ 21 ]. It should be noted that Ser119 is likewise present in drug-resistant strains of HIV-1 subtype C, which most often contain the G118R mutation [ 16 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, information on resistance mutations caused by IN inhibitors in HIV-1 strain FSU-A is limited. To assess the impact of drug resistance mutations on the enzymatic properties of IN of HIV-1 subtype A, we prepared a consensus IN of the FSU-A strain, where RAL- and EVG-resistance mutations were introduced by site-directed mutagenesis [ 21 , 22 ]. The consensus IN sequence of HIV-1 strain FSU-A (INA) differs from the sequence of the best studied IN of HIV-1 subtype B (HXB-2) by substitutions of 16 amino acid residues, nine of which are located in the catalytic domain.…”
Section: Introductionmentioning
confidence: 99%
“…(PLoS One [PONE-D-17-40839] [EMID: 2890cecde7221c73], accepted). Correlation of the loss of photon flux with the anti-Luc response was insignificant (data not shown) due to the low immunogenicity of Luc 31 , 41 , 63 . These observations established in vivo imaging as an animal-sparing method to evaluate the overall performance of DNA immunogens 31 , 41 , 63 .…”
Section: Resultsmentioning
confidence: 98%
“…Based on the prime-boost regimen, we designed experiments to evaluate the effector capacity of the immune response. We have repeatedly shown in previous studies that the cellular immune response can be indirectly monitored in vivo by introducing the DNA immunogen together with a reporter gene, such as firefly luciferase (Luc), with further monitoring of the loss of signal emitted by the reporter 31 , 41 , 63 . We found that the photon flux from the sites of immunogen/reporter gene co-injections is inversely correlated to the cellular immune response against the immunogen 31 , 41 , 63 and Petkov S. et al .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple examples of published literature demonstrate the ability of the ID-EP platform to elicit robust immune responses in a spectrum of animal models 30,[34][35][36][37][38][39] and in the clinic. 28 The use of combination vaccine strategies has a number of clinical benefits.…”
Section: Discussionmentioning
confidence: 99%